2006
DOI: 10.1080/02701367.2006.10599354
|View full text |Cite
|
Sign up to set email alerts
|

Fourth-Grade Students' Motivational Changes in an Elementary Physical Education Running Program

Abstract: Achievement goal theory and the expectancy-value model of achievement choice were used to examine fourth-grade students' motivational changes in an elementary physical education running program. In fall and spring of the school year, participants (N = 113; 66 boys, 47 girls) completed questionnaires assessing achievement goals, expectancy beliefs, subjective task values, and intention for future running participation. They also completed a timed 1-mile (1.6 km) run. The number of laps they ran/walked during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
71
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 38 publications
(52 reference statements)
15
71
6
Order By: Relevance
“…When comparing the intervention group to the control group, significant differences regarding STVs as a dimension were not observed, which corroborates earlier findings among middle-school students (Gao, 2009;Xiang, McBride & Bruene, 2004;Xiang et al, 2006;Xiang et al, 2003). When considering the different dimensions involving STVs, a significant, albeit weak, difference regarding the students' attainment value for PE surfaced, but only among girls.…”
Section: Flipped Learning and Students' Subjective Task Values Of Physupporting
confidence: 79%
See 4 more Smart Citations
“…When comparing the intervention group to the control group, significant differences regarding STVs as a dimension were not observed, which corroborates earlier findings among middle-school students (Gao, 2009;Xiang, McBride & Bruene, 2004;Xiang et al, 2006;Xiang et al, 2003). When considering the different dimensions involving STVs, a significant, albeit weak, difference regarding the students' attainment value for PE surfaced, but only among girls.…”
Section: Flipped Learning and Students' Subjective Task Values Of Physupporting
confidence: 79%
“…feel more competent and perform better on tasks such as dance and gymnastics than boys have (Xiang et al, 2006). However, those trends alone cannot explain the difference detected in the study reported here, since both the intervention and control groups performed the same activities.…”
contrasting
confidence: 55%
See 3 more Smart Citations